The Impact of Microfinance: An Empirical Study of Beneficiary Perspective - Sharma, Monica (Gyan Management Journal, 2015)
TThe objective of the paper is to study the impact of microfinance in India on clients' income level,  educational level, social status and women empowerment. The perspectives of the beneficiaries  regarding the impact of microfinance are further segregated in terms of demographic variables  namely gender, age monthly income and education level. By and large it has been held that  microfinance has brought significant impact on clients' income level, educational level, social status  and women empowerment.
Keywords: Impact of Microfinance; quality life; women empowerment